Effect of Cordyceps spp. and Cordycepin on Functions of Bones and Teeth and Related Processes: A Review - Karol Jędrejko; Katarzyna Kała; Katarzyna Sułkowska-Ziaja; Jolanta Pytko-Polończyk; Bożena Muszyńska (Molecules, 2022)
Cordyceps spp. (belonging to the Ascomycota group) are entomopathogenic mushrooms that have traditionally been used in ethnomedicine in Asian countries such as China, Japan, Korea, and India. They are unique parasites of larvae of selected species of moths. Cordyceps militaris is one of the best sources of cordycepin. Worldwide, osteoporosis is one of the most common bone diseases, whose pharmacotherapy includes various medical interventions; however, the research and development of new molecules and new drugs is required. The impact of adenosine receptors (ARs) on the purinergic signaling pathway may regulate proliferation, differentiate dental pulp stem cells and bone marrow, and modulate osteogenesis and bone repair. The aim of the review was to collect and analyze the available data on the effects of Cordyceps spp. or cordycepin on bone function and related processes. To the best of our knowledge, this is the first systematic review in this perspective, not necessarily using mushroom raw material or even the isolated parent compound cordycepin, but new molecules that are analogs of nucleosides, such as those from C. militaris. This review found that Cordyceps spp. or isolated cordycepin interacts via the AR, 5′ adenosine monophosphate-activated protein kinase (AMPK), and adenosine-5′-triphosphate (ATP) signaling pathway and evaluated their impact on bones, teeth, and dental pulp. Cordyceps spp. was found to have the potential to develop regenerative medicines, thus providing an opportunity to expand the treatment or intervention methods in the recovery after traumatic injuries, convalescence, and terminal-stage or devastating diseases.